New azidometalkojates and their biological activity - Hudecová, D; Jantová, S; Melník, M; Uher, M (Folia microbiologica, 1996)
Azidometalkojates of the general formula MX2 (M = Cu, Mn, Mg, Zn or Ni and X = 5-hydroxy-2-azidomethyl-4H-pyran-4-one) were prepared and tested for antibacterial, antifungal and cytotoxic effects. The mangan and zinc derivatives are not active against any the tested microorganisms. A weak antibacterial activity was found with the copper derivative. The strongest antifungal effects were shown by the nickel derivative while the highest cytotoxic effect on HeLa cells was manifested by the zinc derivative.
Keywords: Antifungal Agents; Fungi; Copper; protinádorové látky; Structure-Activity Relationship; molekulární struktura; antibakteriální látky; Molecular Structure; racionální návrh léčiv; Microbial Sensitivity Tests; Pyrones; antifungální látky; Bacteria; houby; kationty; HeLa buňky; vztahy mezi strukturou a aktivitou; pyrony; Cations; lidé; Anti-Bacterial Agents; HeLa Cells; Humans; mikrobiální testy citlivosti; Drug Design; měď; Antineoplastic Agents